Traditional Fishermen's Productivity Amid Fluctuations in the Increase in Subsidized Fuel Oil - Sugiardi, Sigit (International Journal of Artificial Intelligence Research, 2024)
The purpose of this research is to determine the Productivity of Traditional Fishermen in the Midst of Fluctuations in the Increase in Subsidized Fuel Oil. In this study, the author optimally uses two data sources related to this study, namely. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on Traditional Fishermen Productivity. At the same time, this research is supported (secondary) by other works of thought related to the results of research related to the Fluctuation of Subsidized Fuel Oil Increases. The results of this research are that the fuel subsidy policy has a very important role in supporting the continuity of traditional fishermen's businesses, especially in the face of frequent fluctuations in fuel prices. By reducing operational costs, fuel subsidies help fishermen maintain productivity, improve social welfare, and support the sustainability of the fisheries sector. However, to achieve maximum benefits, it is important for the government to manage subsidies in a targeted, efficient, and supportive manner of using environmentally friendly technologies that reduce dependence on fossil fuels Dependence on fuel oil (BBM) has a major impact on the resilience of the traditional fisheries sector, both in terms of economy and environment. This dependence not only creates dependence on limited natural resources but also increases environmental damage, pollutes waters, and contributes to global warming. Therefore, it is important for fishermen and governments to develop more efficient and environmentally friendly energy alternatives to reduce dependence on fuel and support the sustainability of natural resources and marine ecosystems that depend on environmental balance